2020
DOI: 10.1101/2020.10.05.326652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“A novel female-specific circadian clock mechanism regulating metabolism”

Abstract: Circadian clocks enable organisms to predict and align their behaviors and physiologies to constant daily day-night environmental cycle. Because the ubiquitin ligase Siah2 has been identified as a potential regulator of circadian clock function in cultured cells, we have used Siah2-deficient mice to examine its function in vivo. Our experiments demonstrate a striking and unexpected sexually dimorphic effect of Siah2 deficiency on the regulation of rhythmically expressed genes. The absence of Siah2 in females, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…It may imply that a systemic regulator activates different regulatory pathways for each mouse class as a consequence of different gene expression levels. For instance, it was recently found that ubiquitin associated pathways regulated the cellular clock only in female and not in male mice ( Mekbib et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It may imply that a systemic regulator activates different regulatory pathways for each mouse class as a consequence of different gene expression levels. For instance, it was recently found that ubiquitin associated pathways regulated the cellular clock only in female and not in male mice ( Mekbib et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%